CinemaAfrica 2025/26: A Conversation with ... Ery Claver (Cinema Africa 2025/26, 2026)
Cinema Africa Bayreuth goes into a new round! The first screening took place on 10 November 2025 at Cineplex Bayreuth where a double feature presented two Angolan films "Ar condicionado" and "Our Lady of the Chinese Shop". Ery Claver, who directed the latter and was responsible for cinematography in the former, was present in Bayreuth and answered the questions of the audience. To present two Angolan films to the Bayreuth public could not have come at a better timing as Angola celebrated its 50 anniversary of independence on 11 November 2025. Ery Claver also sat down with Prof. Dr. Ute Fendler, initiator and curator of the Bayreuth film festival, and Adebanjo Oreoluwa Baderin, who is part of the Cinema Africa organisational team to answer their questions on the thoughts that went into making these two special films.